2009 10th Latin American Test Workshop 2009
DOI: 10.1109/latw.2009.4813783
|View full text |Cite
|
Sign up to set email alerts
|

Exploring machine learning techniques for fault localization

Abstract: Debugging is the most important task related to the testing activity. It has the goal of locating and removing a fault after a failure occurred during test. However, it is not a trivial task and generally consumes effort and time. Debugging techniques generally use testing information but usually they are very specific for certain domains, languages and development paradigms. Because of this, a Neural Network (NN) approach has been investigated with this goal. It is independent of the context and presented pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…These individual rankings are then consolidated to form a final statement ranking which can then be examined to locate the faults. There are other studies in this category such as those reported in [3].…”
Section: Machine Learning-based Techniquesmentioning
confidence: 95%
“…These individual rankings are then consolidated to form a final statement ranking which can then be examined to locate the faults. There are other studies in this category such as those reported in [3].…”
Section: Machine Learning-based Techniquesmentioning
confidence: 95%
“…Wong et al (2009; also proposed two neural network-based fault localization techniques trained on program traces. Ascari et al (2009) investigate the use of SVMs in a similar setting.…”
Section: Probabilistic Debugging Methodsmentioning
confidence: 99%
“…Wong et al (2009; also proposed two neural network-based fault localization techniques trained on program traces. Ascari et al (2009) investigate the use of SVMs in a similar setting.…”
Section: Probabilistic Debugging Methodsmentioning
confidence: 99%